Possible mechanism and Atorvastatin-based treatment in cupping therapy-related subdural hematoma: A case report and literature review - Xiang, Tangtang; Zhang, Xinjie; Wei, Yingsheng; Feng, Dongyi; Gong, Zhitao; Liu, Xuanhui; Yuan, Jiangyuan; Jiang, Weiwei; Nie, Meng; Fan, Yibing; Chen, Yupeng; Feng, Jiancheng; et al. (Frontiers in Neurology, 2022)
Subdural hematoma (SDH) is one of the most lethal types of traumatic brain injury. SDH caused by Intracranial Pressure Reduction (ICPR) is rare, and the mechanism remains unclear. Here we report 3 cases of SDH that occurred after substandard cupping therapy and are conjected to be associated with ICPR. All of them had undergone cupping treatments. On the last cupping procedure, they experienced a severe headache after the cup placed on the occipital-neck junction (ONJ) was suddenly removed and were diagnosed with SDH the next day. In standard cupping therapy, the cups are not usually placed on the ONJ. We speculate that removing these cups on the soft tissue over the cisterna magna repeatedly created localized negative pressure, caused temporary but repeated ICPR, and eventually led to SDH development. The Monro-Kellie Doctrine can explain the mechanism behind this - it states that the intracranial pressure is regulated by a fixed system, with any change in one component causing a compensatory change in the other. The repeated ICPR promoted brain displacement, tearing of the bridging veins, and development of SDH. The literature was reviewed to illustrate the common etiologies and therapies of secondary ICPR-associated SDH. Despite the popularity of cupping therapy, its side effects are rarely mentioned. This case is reported to remind professional technicians to fully assess a patient's condition before cupping therapy and ensure that the cups are not placed at the ONJ.